2001
DOI: 10.1590/s1516-44462001000400008
|View full text |Cite
|
Sign up to set email alerts
|

Tradução e adaptação para o português da Escala de Compulsão Alimentar Periódica

Abstract: . *O termo da língua inglesa binge eating não tem tradução exata em português. Adotou-se a tradução "compulsão periódica", da versão para o português do DSM-IV, acrescentando a palavra "alimentar" para que ficasse explícito tratar-se de comportamento alimentar. Resumo Descritores Abstract KeywordsIntrodução/Objetivos: Descreve-se o processo de tradução e adaptação, para a língua portuguesa, da Binge Eating Scale (BES) -Escala de Compulsão Alimentar Periódica (ECAP) -, que avalia a gravidade da compulsão alimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
52

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(142 citation statements)
references
References 11 publications
3
79
0
52
Order By: Relevance
“…3 Despite the measurements of weight and height not having been verified when the study was carried out, but reported by the students, which could be considered a limiting factor for the data reliability, a study performed with 1,157 men and women, aged between 15-64 years, showed that there is an association between the self-reported weight and the weight measured by the researchers. 23 Another aspect that should be stressed as limitation was the divergence in the proportions of losses between the fields of study, once the students of humanities and exact sciences seem to have had less understanding or involvement with the objective of the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Despite the measurements of weight and height not having been verified when the study was carried out, but reported by the students, which could be considered a limiting factor for the data reliability, a study performed with 1,157 men and women, aged between 15-64 years, showed that there is an association between the self-reported weight and the weight measured by the researchers. 23 Another aspect that should be stressed as limitation was the divergence in the proportions of losses between the fields of study, once the students of humanities and exact sciences seem to have had less understanding or involvement with the objective of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument used to evaluate BE was the Binge Eating Scale (BES), which was translated and validated into Portuguese. 3 Besides the 16 questions that were part of the BES, another question was added to evaluate the student's perception with regard to the occurrence of moments of excessive food intake in a short period of time. If the student answered yes, there was an option to report the frequency: once a month, twice a month, once a week, twice or more times a week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the cutoff point C12 was used to define depression. Binge eating disorder was assessed by the Portuguese version of the BES [29]. This is a 16-item questionnaire whose questions are based on behavioral and the emotional characteristics (guilt or shame).…”
Section: Study Protocolmentioning
confidence: 99%